Burial or cremation? Factors associated with preferences among patients with cancer in Brazil: a cross-sectional study - Paiva, Bianca Sakamoto Ribeiro; Lourenço, Bruna Minto; Prata, Henrique Moraes; Valentino, Talita Caroline de Oliveira; Oliveira, Marco Antonio de; Santos Neto, Martins Fideles dos; Bruera, Eduardo; Paiva, Carlos Eduardo (São Paulo Medical Journal, 2023)
BACKGROUND: People living with life-limiting illnesses and their family caregivers consistently emphasize the importance of preparing for imminent death, with planned funerals being a common aspect of this preparation. Few studies have described the funeral rituals or post-mortem preferences of patients with cancer. OBJECTIVE: To evaluate the percentage of patients with cancer who wish to be cremated and to identify the factors associated with this preference. DESIGN AND SETTING: Cross-sectional study conducted at Barretos Cancer Hospital. METHODS: A total of 220 patients with cancer completed a Sociodemographic and Clinical Questionnaire, the Duke University Religiosity Index, and burial or cremation preferences. Binary Logistic Regression was performed to identify independent variables associated with cremation. RESULTS: Of the 220 patients, 25.0% preferred cremation and 71.4% preferred burial. Talks about death with family or close friends in their daily life (odds ratio, OR = 2.89; P = 0.021), patients that answered “other” (unsure, tends not be true and not true) for religious beliefs are what really lie behind my whole approach to life (OR = 20.34; P = 0.005), and education 9 to 11 years (OR = 3.15; P = 0.019) or ≥ 12 years (OR = 3.18; P = 0.024) were associated with cremation preference. CONCLUSION: Most patients with Cancer in Brazil prefer burial after death. Discussions about death, religious beliefs and involvement, and educational level seem to influence the preference for cremation. A deeper understanding of ritual funeral preferences and their associated factors may guide policies, services, and health teams in promoting the quality of dying and death.